(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
New service development is increasingly becoming one of the most important aspects of business strategy in both service and non-service industries. In todays economical world where has become more service oriented, it can be said that the new service development (NSD) is one of the most important components of growth in dynamic environments. As new proposals lead to an increase in income, profit and develop in market share. The aim of the study was to survey new service development and factors affecting its financial performance in banking industry. In terms of research philosophy this is a demonstrative, in terms of research purpose and direction it’s a practical and descriptive, and in terms of research implementation strategy it’s a survey research that has been executed in cross-sectional time period. The purpose of the research sampling was to examine the new services, which are provided in the various banks. Stratified probability sampling method used is based on 150 questionnaires in headquarters and branches of different banks, which are located in Tehran city, and 118 questionnaires were gathered. Data obtained from the questionnaires were analyzed in both descriptive and inferential level by using SPSS version 21 and Lisrel 8.8 Windows version. Structural equation modeling techniques (confirmatory factor analysis and structural analysis) have been used to test the research hypotheses. Results of the research showed that cross-functional teams and learning orientation have positive impact on the new service marketability. And indirectly have a positive impact on the financial performance of new service. Customer involvement and learning orientation have positive impact on the new service launch preparation, but the effect of new service launch preparation on new service financial performance has not been proved in the current study.